2019
DOI: 10.1016/j.ajhg.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance

Abstract: Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 70 publications
6
92
0
Order By: Relevance
“…Oligogenic inheritance, characterized by the concurrent effect of two or more distinct genes on the resulting phenotype, was subsequently confirmed to apply to other skeletal deformities such as arthrogryposis [45]. Based on the results from previous studies and our findings, the etiology of congenital cervical fusion is unlikely to be fully explained by a monogenetic model for a fraction of patients.…”
Section: Discussionsupporting
confidence: 75%
“…Oligogenic inheritance, characterized by the concurrent effect of two or more distinct genes on the resulting phenotype, was subsequently confirmed to apply to other skeletal deformities such as arthrogryposis [45]. Based on the results from previous studies and our findings, the etiology of congenital cervical fusion is unlikely to be fully explained by a monogenetic model for a fraction of patients.…”
Section: Discussionsupporting
confidence: 75%
“…For some disorders, the discovery of rare genetic variants and the observation of familial co-segregation in some cases result in the perception that Mendelian inheritance may apply. However, recent advances in genetic tests have revealed several disorders beyond the One Gene-One Disease paradigm, indicatinga more complex inheritance and pleiotropy in heritable disorders [13]. Cerrone et al, reported that oligogenic or polygenic genetic variants contributed to inheritable cardiac disorders [14].…”
Section: Discussionmentioning
confidence: 99%
“…SPTBN4 (Spectrin Beta, Non-Erythrocytic 4) is a protein coding gene, which is, according to the Human Protein Atlas, primary expressed in brain tissue and particularly in the cerebellum, which is the part of the brain that functions as a co-processor of movement in concert with the cortex and basal ganglia 52 . In line, mutations and loss-of-function variants in SPTBN4 were reported in association with arthrogryposis, which is a neuromuscular condition 53 , and with a severe neurological syndrome that includes congenital hypotonia, intellectual disability, and motor axonal and auditory neuropathy 54 . To the best of our knowledge, only one study has identified differential DNA methylation in SPTBN4 in association with neurocognitive outcomes (Alzheimer's disease) and this study was conducted in mice 55 .…”
Section: Differential Methylation In Sptbn4 and Nbpf8 As An Early Sigmentioning
confidence: 93%